The Cost-effectiveness of a Point-of-Care Paper Transaminase Test for Monitoring Treatment of HIV/TB Co-Infected Persons. (8th September 2017) - Rajasingham, Radha; Pollock, Nira R; Linas, Benjamin P
Abstract: Background: Persons with HIV and tuberculosis (TB) co-infection require transaminase monitoring while on hepatotoxic medications. A novel paper-based, point-of-care transaminase test is in development at an anticipated cost of 1 per test. Methods: To project long-term clinical outcomes and estimate the cost-effectiveness of using a paper-based fingerstick test to monitor for drug-induced liver injury (DILI), as compared with automated testing and with no laboratory monitoring. The design was a decision analytic model, including deterministic and probabilistic sensitivity analyses. Data sources were observational cohorts and a validation study of the paper-based test. The target population was HIV/TB co-infected persons in South Africa on antiretroviral therapy who were initiating TB therapy. Interventions: (1) clinical (no laboratory) monitoring; (2) monitoring using the paper-based test with a ≥120 IU/mL threshold for positivity; (3) monitoring using the paper-based test with a ≥200 IU/mL threshold for positivity; (4) monitoring using the paper-based test using 1 of 3 categories: <120 IU/mL, 120 to 200 IU/mL, and >200 IU/mL ("bin placement"); (5) monitoring using automated ALT testing using the same 3 categories ("automated testing"). The outcome measures were discounted quality-adjusted life-years (QALYs), costs, and incremental cost-effectiveness ratios (ICERs). Results: The ICER of automated testing was 5180/QALY. Use of the paper-based test with the bin placement strategy was cost-effective compared with clinical monitoring alone. Conclusion: At its current performance, monthly DILI monitoring by bin placement using the paper-based test was cost-effective, compared with clinical monitoring, in HIV/TB co-infected persons in South Africa.